Soft magnetic metal powder, soft magnetic metal fired body, and coil-type electronic component

By using soft magnetic metal powder of Fe-Ni-Si-M alloy or Fe-Ni alloy, combined with resin filling technology, the problem of insufficient inductance and Q value in coil-type electronic components is solved, and high magnetic permeability and The soft magnetic metal sintered body with high resistivity avoids short circuits and plating elongation, and improves the performance of electronic components.

CN119237721APending Publication Date: 2025-01-03TDK CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411421438.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-09-26
Filing Date
2020-09-25
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The prior art is difficult to provide a soft magnetic metal sintered body with sufficiently high inductance L and Q values ​​and which is not prone to short-circuiting, and has a low magnetic permeability μ and resistivity ρ.

Method used

A soft magnetic metal powder consisting of Fe-Ni-Si-M alloy or Fe-Ni alloy, the alloy contains P, and M is selected from B, Co, Mn, Ti, Zr, Hf, Nb, Ta, Mo , Mg, Ca, Sr, Ba, Zn, Al and rare earth elements, elements are sintered to form soft magnetic metal sintered bodies with high permeability and high resistivity, and the gap space is filled with resin in coil-type electronic components. to increase inductance and Q value.

Benefits of technology

The inductance L and Q values ​​are improved, plating elongation and short circuit are avoided, and the magnetic permeability μ and resistivity ρ are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237721A_ABST
    Figure CN119237721A_ABST
Patent Text Reader

Abstract

[Problem] To provide a soft magnetic metal powder or the like capable of providing a soft magnetic metal fired body having a high magnetic permeability [mu] and resistivity [rho], the soft magnetic metal fired body being included in a coil-type electronic component that has sufficiently high inductance L and Q values, is not susceptible to plating elongation, and is not susceptible to short-circuiting. [Solution] This soft magnetic metal powder contains soft magnetic metal particles containing at least Fe and Ni. And further comprises P, Si, Cr and / or M. M is one or more elements selected from the group consisting of B, Co, Mn, Ti, Zr, Hf, Nb, Ta, Mo, Mg, Ca, Sr, Ba, Zn, Al, and rare earth elements. The content of each element is within a predetermined range.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] (This application is a divisional application of a patent application with a filing date of September 25, 2020, application number 202080066068.3, and invention name “Soft Magnetic Metal Powder, Soft Magnetic Metal Sintered Body, and Coil-Type Electronic Component”.) Technical Field

[0002] The present invention relates to soft magnetic metal powder, soft magnetic metal sintered body and coil type electronic component. Background Art

[0003] Patent Document 1 discloses an invention related to a laminated coil, which is characterized in that a resin is impregnated into gaps between Fe-Si-Cr alloy particles in a magnetic body.

[0004] Patent Document 2 discloses an invention relating to a soft magnetic alloy powder, which is characterized by containing Fe-Ni based particles in which the contents of Fe, Ni, Co and Si are controlled within specific ranges.

[0005] Prior art literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2012-238840

[0007] Patent Document 2: Japanese Patent Application Publication No. 2008-135674 Summary of the invention

[0008] The technical problem that the invention is intended to solve

[0009] The object of the present invention is to provide a soft magnetic metal powder, etc., which can provide a soft magnetic metal sintered body with high magnetic permeability μ and resistivity ρ, which can be included in a coil-type electronic component with sufficiently high inductance L and Q value, and which is less likely to produce plating elongation and is not prone to short circuit.

[0010] Means for solving technical problems

[0011] The soft magnetic metal powder involved in the first aspect of the present invention comprises soft magnetic metal particles composed of a Fe-Ni-Si-M alloy, wherein the Fe-Ni-Si-M alloy further comprises P, and M is one or more selected from B, Co, Mn, Ti, Zr, Hf, Nb, Ta, Mo, Mg, Ca, Sr, Ba, Zn, Al and rare earth elements. In the Fe-Ni-Si-M alloy, based on the total content of Fe, Ni, Si and M as 100 mass%, the alloy comprises Ni of 15.0 mass% or more and 55.0 mass% or less, Si of 2.0 mass% or more and 6.0 mass% or less, M of 2.0 mass% or more and 40.0 mass% or less, and P of 100 ppm or more and 5000 ppm or less.

[0012] The soft magnetic metal powder involved in the second aspect of the present invention comprises soft magnetic metal particles composed of an Fe-Ni alloy, wherein the Fe-Ni alloy further comprises Cr, and the Fe-Ni alloy further comprises Si and / or M, wherein M is one or more selected from B, Co, Mn, Ti, Zr, Hf, Nb, Ta, Mo, Mg, Ca, Sr, Ba, Zn, Al and rare earth elements, and in the Fe-Ni alloy, the total content of Fe, Ni, Si, M and Cr is 100 mass%, and the Cr content is less than 2.0 mass%.

[0013] The Fe-Ni alloy may further contain P. In the Fe-Ni alloy, the total content of Fe, Ni, Si, M and Cr is 100 mass %, and P may be contained in an amount of 100 ppm to 5000 ppm both inclusive.

[0014] The following description is common to the soft magnetic alloy powder according to the first aspect and the soft magnetic metal powder according to the second aspect.

[0015] M can be Co.

[0016] The soft magnetic metal powder may have an average particle size (D50) of 1.5 μm or more and 15.0 μm or less.

[0017] The soft magnetic metal sintered body according to the first and second aspects of the present invention includes the soft magnetic metal powder according to the first and second aspects.

[0018] The soft magnetic metal sintered body including the soft magnetic metal powder tends to have high magnetic permeability μ and resistivity ρ.

[0019] The coil type electronic component according to the first and second aspects of the present invention comprises a magnetic body and a coil conductor built in the magnetic body, wherein the magnetic body is formed of the soft magnetic metal sintered body according to the first and second aspects.

[0020] The coil type electronic component whose magnetic body is composed of the above-mentioned soft magnetic metal sintered body has sufficiently high inductance L and Q value, is less likely to cause plating elongation and short circuit.

[0021] The soft magnetic metal particles may be covered with a coating film, and a layer of the coating film that is in contact with the soft magnetic metal particles may contain Si or an oxide containing Si.

[0022] The layer in contact with the soft magnetic metal particles in the coating film may further contain P.

[0023] The coating film may have an average thickness of 5 nm or more and 60 nm or less.

[0024] The coil-type electronic component involved in the third aspect of the present invention is a coil-type electronic component having a magnetic body and a coil conductor built into the above-mentioned magnetic body, the above-mentioned magnetic body contains soft magnetic metal particles, the Cr content in the above-mentioned soft magnetic metal particles is less than 2.0 mass% (excluding 0 mass%), the above-mentioned soft magnetic metal particles are coated with a coating film, the above-mentioned coating film is composed of a first layer in contact with the above-mentioned soft magnetic metal particles and a second layer connected to the above-mentioned first layer, the above-mentioned first layer contains Si or an oxide containing Si, and the above-mentioned second layer contains Cr.

[0025] Alternatively, the average thickness of the first layer may be D1, the average thickness of the second layer may be D2, and 0.5≤D2 / D1≤1.5.

[0026] D2 may be greater than or equal to 2.5 nm and less than or equal to 30 nm.

[0027] The following description is common to all the coil type electronic components described above.

[0028] The magnetic body may include soft magnetic metal particles and a resin, and the resin may be filled in gaps between the soft magnetic metal particles.

[0029] The above resin may be a phenolic resin or an epoxy resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a laminated coil according to one embodiment of the present invention.

[0031] Figure 2 It is a schematic cross-sectional view of a magnetic body.

[0032] Figure 3 This is a SEM image of the interlayer portion in Example 103.

[0033] Figure 4 This is a SEM image of the interlayer portion in Example 104.

[0034] Figure 5 This is the BF image in Example 103.

[0035] Figure 6 This is the BF image in Example 103.

[0036] Figure 7 This is the C mapping image in Example 103.

[0037] Figure 8 This is the C mapping image in Example 103.

[0038] Fig. 9This is the Si mapping image in Example 103.

[0039] Fig.10 This is the Si mapping image in Example 103.

[0040] Fig.11 It is the O mapping image in Example 103.

[0041] Fig.12 It is the O mapping image in Example 103.

[0042] Fig.13 It is a schematic cross-sectional view of the soft magnetic metal particles in the magnetic body.

[0043] Explanation of symbols

[0044] 1...Laminated coil

[0045] 2……Components

[0046] 2a……Surface

[0047] 2b...Central

[0048] 3……Terminal electrode

[0049] 4……Magnetic body

[0050] 4a...Interlayer

[0051] 5... Coil conductor

[0052] 5a, 5b...lead-out electrodes

[0053] 11... Soft magnetic metal particles

[0054] 11a……Soft magnetic metal particles

[0055] 11b……Oxide coating

[0056] 12…Interstitial Space

[0057] 13. Resin

[0058] 14... Gap DETAILED DESCRIPTION

[0059] Hereinafter, the present invention will be described based on the embodiments shown in the drawings.

[0060] <Soft Magnetic Metal Powder>

[0061] (First Embodiment)

[0062] The soft magnetic metal powder involved in the first embodiment is an aggregate of multiple soft magnetic metal particles. The soft magnetic metal particles are composed of Fe-Ni-Si-M alloy. The Fe-Ni-Si-M alloy further contains P. M is one or more selected from B, Co, Mn, Ti, Zr, Hf, Nb, Ta, Mo, Mg, Ca, Sr, Ba, Zn, Al and rare earth elements. M is preferably Co. In this embodiment, in the Fe-Ni-Si-M alloy, the total content of Fe, Ni, Si and M is set to 100% by mass, and the content of other elements, except P and O, can be 0.15% by mass or less. The content of O can be 0.5% by mass or less. The content of Cr can be less than 0.1% by mass, or it can be less than 0.03% by mass.

[0063] Furthermore, the content of Ni is 15.0 mass % or more and 55.0 mass % or less, the content of Si is 2.0 mass % or more and 6.0 mass % or less, and the content of M is 2.0 mass % or more and 40.0 mass % or less. Furthermore, the content of P is 100 ppm or more and 5000 ppm or less, that is, 0.0100 mass % or more and 0.5000 mass % or less.

[0064] The content of Ni may be 22.0% by mass or more and 42.0% by mass or less. The content of Si may be 2.5% by mass or more and 5.5% by mass or less, or 2.5% by mass or more and 4.0% by mass or less. The content of M may be 5.0% by mass or more and 32.0% by mass or less. The content of P may be 300 ppm or more and 2000 ppm or less.

[0065] By using soft magnetic metal powder composed of soft magnetic metal particles having the above-mentioned composition to produce a soft magnetic metal sintered body, a soft magnetic metal sintered body with higher magnetic permeability μ and resistivity ρ can be obtained compared with the case where a soft magnetic metal sintered body is produced using soft magnetic metal powder composed of soft magnetic metal particles not having the above-mentioned composition.

[0066] In particular, when the Si content is too low, the resistivity tends to decrease because it is difficult to appropriately maintain the oxidation state of the soft magnetic metal particles after the heat treatment.

[0067] The average particle size (D50) of the soft magnetic metal powder involved in this embodiment can be greater than 1.5 μm and less than 15.0 μm, or greater than 2.0 μm and less than 15.0 μm, or greater than 5.0 μm and less than 10.0 μm. By making the average particle size of the soft magnetic metal powder within the above range, it is easy to obtain a soft magnetic metal sintered body with high magnetic permeability μ and resistivity ρ. There is no particular restriction on the method for determining the average particle size (D50). For example, a laser diffraction scattering method can be used. It should be noted that the shape of the soft magnetic metal particles constituting the soft magnetic metal powder is not particularly limited.

[0068] <Soft Magnetic Metal Sintered Body>

[0069] The soft magnetic metal sintered body involved in this embodiment has a structure in which a plurality of soft magnetic metal particles are connected to each other by sintering. Specifically, the elements contained in the soft magnetic metal particles that are in contact with each other by sintering react with other elements (e.g., O), and a plurality of soft magnetic metal particles are connected to each other via bonds caused by the reaction. In the soft magnetic metal sintered body involved in this embodiment, the soft magnetic metal particles from the soft magnetic metal powder are connected to each other by heat treatment, but each soft magnetic metal particle hardly undergoes grain growth. That is, the particle size of each soft magnetic metal particle hardly changes.

[0070] It should be noted that the particle size of the soft magnetic metal particles contained in the soft magnetic metal sintered body can be calculated by performing image analysis on the cross-section of the soft magnetic metal sintered body using SEM or STEM, etc. to calculate the area of ​​the soft magnetic metal particles, and the value is calculated as the diameter of a circle equivalent to the area (equivalent circle diameter).

[0071] The composition and particle size of the soft magnetic metal particles contained in the soft magnetic metal sintered body are the same as those of the soft magnetic metal powder described above, except for the content of O. The content of O may be 0.5 mass % or less.

[0072] <Coil type electronic components>

[0073] The coil type electronic component according to the present embodiment may be a stacked coil type electronic component. Figure 1 The stacked coils shown.

[0074] like Figure 1As shown, the laminated coil 1 of this embodiment has an element 2 and a terminal electrode 3. The element 2 has a structure in which a coil conductor 5 is buried three-dimensionally and spirally inside a magnetic body 4. Terminal electrodes 3 are formed at both ends of the element 2, and the terminal electrodes 3 are connected to the coil conductor 5 via lead electrodes 5a and 5b. In addition, the element 2 is composed of a central portion 2b in which the coil conductor 5 is buried, and a surface portion 2a that exists above and below the central portion 2b in the stacking direction (z-axis direction) and in which the coil conductor 5 is not buried. In addition, in this embodiment, the middle portion between the coil conductors 5 in the stacking direction in the magnetic body 4 is set as an interlayer portion 4a.

[0075] The shape of the element 2 is arbitrary, but is usually a rectangular parallelepiped. In addition, its size is not particularly limited and can be set to an appropriate size according to the application. For example, it can be 0.2 to 2.5 mm×0.1 to 2.0 mm×0.1 to 1.2 mm.

[0076] The material of the terminal electrode 3 is not particularly limited as long as it is a conductor. For example, Ag, Cu, Au, Al, Ag alloy, Cu alloy, etc. can be used. In particular, Ag is cheap and has low resistance, so it is preferably used. The terminal electrode 3 may contain glass powder. In addition, the terminal electrode 3 may also have a two-layer structure of a metal layer formed on the element 2 and composed of the above-mentioned metal, or the above-mentioned metal and glass powder, and a resin layer formed on the metal layer and composed of a conductive resin. The type of metal contained in the conductive resin is not particularly limited. For example, Ag can be cited. In addition, the terminal electrode 3 may also be plated on the surface. For example, Cu plating, Ni plating and / or Sn plating may also be appropriately implemented.

[0077] The coil conductor 5 and the lead electrodes 5a and 5b may be made of any material as long as they are conductive. For example, Ag, Cu, Au, Al, Ag alloy, Cu alloy, etc. may be used. In particular, Ag is preferably used because it is inexpensive and has low resistance.

[0078] like Figure 2 As shown, the magnetic body 4 can be composed of soft magnetic metal particles 11 and resin 13. The presence of the resin 13 can easily increase the inductance L and the Q value. Furthermore, the laminated coil is less likely to short-circuit. Figure 2 1 is a schematic cross-sectional view of the magnetic body 4. In addition, the portion other than the soft magnetic metal particles 11 in the magnetic body 4 is set as a gap space 12. Then, the gap space 12 is filled with a resin 13, and the portion not filled with the resin 13 becomes a void 14. In addition, before the resin is filled, the gap space 12 is entirely a void 14.

[0079] The soft magnetic metal particles 11 may also be coated with a coating film. Fig.13As shown, the soft magnetic metal particles 11 may be composed of a soft magnetic metal particle body 11a and an oxide film 11b coating the soft magnetic metal particle body 11a. Furthermore, the oxide film 11b coating the soft magnetic metal particle body 11a of the present embodiment preferably includes a layer composed of an oxide containing Si, and the soft magnetic metal particle body 11a is preferably in contact with the layer composed of an oxide containing Si. By the oxide film 11b coating the soft magnetic metal particle body 11a including a layer composed of an oxide containing Si, the insulation between the soft magnetic metal particles 11 is increased, thereby improving the Q value. In addition, by the oxide film 11b coating the soft magnetic metal particle body 11a including a layer composed of a compound containing Si, the formation of Fe oxide can also be prevented.

[0080] The soft magnetic metal particle body 11a is composed of the above-mentioned Fe-Ni-Si-M alloy. In particular, it is considered that when the content of P is within a specified range, the oxidation state of the soft magnetic metal particles 11 constituting the magnetic body 4 after heat treatment, that is, the coverage rate or thickness of the oxide film 11b, etc. can be appropriately controlled. In the case where the layer composed of the above-mentioned Si-containing oxide further contains P, the coverage rate or thickness of the oxide film 11b is more easily appropriately controlled. As a result, the magnetic body 4 after heat treatment exhibits a high resistivity and can exert the specified magnetic properties. Therefore, the magnetic body 4 of this embodiment is suitable as a magnetic body that is in direct contact with the coil conductor 5.

[0081] The type of resin 13 is arbitrary. It may be phenolic resin or epoxy resin. When the resin 13 is phenolic resin or epoxy resin, it is easy to fill the gap 12 with the resin 13. In addition, when the resin 13 is phenolic resin, it is inexpensive and easy to handle, so it is preferred.

[0082] By filling the gap space 12 with resin 13, the strength (particularly bending strength) of the laminated coil 1 is increased. In addition, the insulation between the soft magnetic metal particles 11 is further improved, and the inductance L and Q value are easily increased. Furthermore, the reliability and heat resistance are improved.

[0083] Here, the interlayer portion 4a is the part of the element 2 of the laminated coil 1 where the resin 13 is most difficult to fill into the gap space 12. Therefore, if the gap space 12 of the interlayer portion 4a is filled with resin 13, it can be said that the entire element 2 of the laminated coil 1 is fully filled with resin 13.

[0084] There is no particular limitation on the method for confirming whether the oxide film 11b covering the soft magnetic metal particle body 11a includes a layer composed of an oxide containing Si and whether the resin 13 is filled in the gap space 12. For example, by performing SEM-EDS measurement and STEM-EDS measurement, it is possible to visually confirm whether the oxide film 11b covering the soft magnetic metal particle body 11a includes a layer composed of an oxide containing Si and whether the resin 13 is filled in the gap space 12.

[0085] Here, Figure 3 is a SEM image of the interlayer portion of Example 103 described later. Figure 4 This is a SEM image (magnification 10000 times) of the interlayer portion of Example 104 described later. Figure 3 and Figure 4 It can be seen that resin exists in addition to the soft magnetic metal particles and fills the gap space.

[0086] further, Figure 5 to Figure 12 This is a drawing showing the STEM-EDS measurement results of the interlayer portion of Example 103 described later. Figure 5 This is a bright field image (BF image) obtained using STEM (magnification 20,000 times). Figure 6 This is a bright field image (BF image) obtained using STEM (magnification: 500,000 times). Figure 7 This is a C mapping image obtained using STEM-EDS (magnification 20,000 times). Figure 8 This is a C mapping image obtained using STEM-EDS (magnification 500,000 times). Fig. 9 This is a Si mapping image obtained by STEM-EDS (magnification 20,000 times). Fig.10 This is a Si mapping image obtained by STEM-EDS (magnification 500,000 times). Fig.11 This is an O mapping image obtained using STEM-EDS (magnification 20,000 times). Fig.12 This is an O mapping image obtained using STEM-EDS (magnification 500,000 times).

[0087] Depend on Figure 5 to Figure 12 It is known that the resin 13 is filled in the interstitial space 12 of the interlayer portion and is cured. Furthermore, it is known that Si exists substantially only in the soft magnetic metal particles 11 and C exists substantially only in the interstitial space 12 .

[0088] In addition, in Example 103 described later, Fig.13As shown, there is an oxide film 11b covering the soft magnetic metal particle body 11a. The oxide film 11b includes a Si oxide layer. Si substantially exists only in the soft magnetic metal particle body 11a and the oxide film 11b. In addition, Si oxide substantially exists only in the oxide film 11b. It should be noted that the Si oxide layer 11b is a layer mainly composed of Si oxide.

[0089] It should be noted that the thickness of the oxide film 11b is not particularly limited. The Si oxide layer may also be in contact with the soft magnetic metal particle body 11a. For example, the oxide film 11b may be composed only of a Si oxide layer, or may be a multilayer structure of a Si oxide layer and other oxide layers. The Si oxide layer in contact with the soft magnetic metal particle body 11a is essentially composed only of Si oxide. The thickness of the oxide film 11b and the thickness of each layer can be measured using a STEM-EDS measurement image. In this embodiment, the average thickness of the coating layer, that is, the average thickness of the entire oxide film 11b can be greater than 5nm and less than 60nm. It should be noted that the above average thickness is the average value of the thickness when the thickness of the oxide film 11b is measured for at least 50 soft magnetic metal particles 11.

[0090] There is no particular limitation on the method for forming the oxide film 11b. For example, it can be formed by sintering the soft magnetic metal powder involved in this embodiment. In addition, the thickness of the oxide film 11b and the thickness of each oxide layer can be controlled by sintering conditions such as sintering temperature or time or annealing conditions. It should be noted that the thicker the oxide film 11b and the smaller the gap space 12, the lower the filling amount of the resin 13. In addition, it is preferred that the oxide of Si is substantially contained only in the oxide film 11b, and is almost non-existent in the portion (gap space 12) between the two soft magnetic metal particles 11 on the outside of the oxide film 11b.

[0091] In the laminated coil 1 of the present embodiment, the resistivity of the soft magnetic material (soft magnetic metal particles 11) constituting the magnetic body 4 is high. This is because the soft magnetic metal particle body 11a is coated with the oxide film 11b. Furthermore, when the gap space 12 is filled with the resin 13, it is difficult for the plating liquid to invade the gap space 12. Therefore, when filled with the resin 13, it is difficult to short-circuit even after plating, and it is easy to have a high inductance L. Furthermore, the strength (especially the bending strength) of the laminated coil 1 is also improved.

[0092] In addition, the area ratio of the gap space 12 in the cross section of the interlayer portion 4a (central portion 2b) is preferably greater than 5.0% and less than 35.0% relative to the entire SEM observation image. In addition to being able to control the area ratio of the gap space 12 by the particle size distribution of the soft magnetic metal particles, it can also be controlled by controlling the amount of binder resin in the green chip, the molding pressure when forming the green chip, the firing conditions, the annealing conditions, etc. In addition, if the average particle size (D50) of the soft magnetic metal particles is the same, there is a tendency that the larger the gap space and the more resin is filled, the smaller the inductance L becomes, but the Q value and the bending strength become larger.

[0093] <Method for producing soft magnetic metal powder>

[0094] An example of a method for producing soft magnetic metal powder is described. In the present embodiment, the soft magnetic metal powder can be obtained using the same method as the known method for producing soft magnetic metal powder. Specifically, the soft magnetic metal powder can be produced using a gas atomization method, a water atomization method, a rotating disk method, etc. Among them, from the viewpoint of easily obtaining a soft magnetic metal powder having desired magnetic properties, it is preferred to use a water atomization method.

[0095] In the water atomization method, a molten raw material (molten metal) is supplied as a linear continuous fluid through a nozzle provided at the bottom of a crucible, and high-pressure water is blown onto the supplied molten metal to dropletize the molten metal and rapidly cool it to obtain a fine powder.

[0096] In the present embodiment, for example, raw materials of Fe, Ni, Si and Co are melted, and a substance to which P is added is pulverized by water atomization, thereby manufacturing the soft magnetic metal powder involved in the present embodiment. In addition, in the case where P is contained as an impurity in the raw material, for example, in the raw material of Fe, the content of P as an impurity and the total amount of P added can be adjusted to manufacture a soft magnetic metal powder containing a target amount of P. Alternatively, a plurality of Fe raw materials having different P contents can be used, and the melt with the adjusted P content can be pulverized by water atomization.

[0097] <Method for producing soft magnetic metal sintered body and coil type electronic component>

[0098] First, an example of a method for manufacturing a soft magnetic metal sintered body according to the present embodiment is described. A binder is added to the soft magnetic metal powder obtained by the above method to prepare granulated powder. There is no particular restriction on the type of binder. For example, acrylic resin can be cited. The obtained granulated powder is molded to obtain a molded body. There is no particular restriction on the molding pressure. For example, it can also be 3 ton / cm 2 Above and 10ton / cm 2Below. Next, the binder is removed. There is no particular restriction on the holding temperature and holding time during the binder removal. For example, it can also be set to be above 300°C and below 450°C, and above 0.5 hours and below 2.0 hours. Next, the molded body after the binder removal is sintered to obtain a soft magnetic metal sintered body. There is no particular restriction on the type of reducing atmosphere. For example, a mixed gas atmosphere of N2 gas and H2 gas with a hydrogen concentration of 0.1% to 3.0% can be cited. There is no particular restriction on the sintering temperature and sintering time. For example, it can be set to be above 550°C and below 850°C, and above 0.5 hours and below 3.0 hours. The longer the sintering time and the lower the hydrogen concentration in the reducing atmosphere, the thicker the thickness of the coating (oxide film 11b) coating the soft magnetic metal powder.

[0099] When using a soft magnetic metal powder of the Fe-Si-Cr system mainly containing Fe, Si, and Cr and having a small content of other elements such as Ni and M, the resistivity is increased by sintering at 400 to 900°C in an atmosphere containing oxygen. This is to form an oxide film with high insulation properties composed of Si and / or Cr. However, when using the soft magnetic metal powder involved in this embodiment, iron oxide is likely to be preferentially generated when sintering is performed in an atmosphere containing oxygen. As a result, the resistivity of the soft magnetic metal powder is reduced, and the inductance L of the coil-type electronic component finally obtained is reduced.

[0100] Furthermore, the obtained soft magnetic metal sintered body may be subjected to annealing (heat treatment). The conditions for the annealing are not particularly limited. For example, it may be set to be above 500°C and below 800°C, and above 0.5 hours and below 2.0 hours. The atmosphere during the heat treatment is also not particularly limited. For example, it may be set to an atmosphere with an oxygen concentration of above 0.05% and below 21.0%.

[0101] In addition, the binder removal and sintering can be performed in an oxidizing atmosphere such as in the air. However, it is preferably performed in an atmosphere with a weaker oxidizing force than the air atmosphere, such as a nitrogen atmosphere or a mixed atmosphere of nitrogen and hydrogen. In this way, the resistivity of the soft magnetic metal particles can be maintained at a high level, while the density of the magnetic body can be increased, and the magnetic permeability can be further increased. In addition, it is easy to form a Si oxide film on the surface of the soft magnetic metal particles, and it is difficult to form Fe oxide. As a result, the reduction of inductance L caused by the oxidation of Fe can be prevented.

[0102] It should be noted that the amount of P contained in the soft magnetic metal particles after the heat treatment is consistent with the amount of P contained in the soft magnetic metal particles before the heat treatment.

[0103] Furthermore, a coil type electronic component can be obtained by winding a coil etc. around the obtained soft magnetic metal sintered body. The method for producing the coil type electronic component is not particularly limited, and a method used in the art can be used.

[0104] <Method for manufacturing laminated coil type electronic component>

[0105] As an example of a method for manufacturing a laminated coil type electronic component, Figure 1 The manufacturing method of the stacked coil type electronic component shown in the figure is described. First, the obtained soft magnetic metal powder is slurried together with additives such as a solvent and an adhesive to make a paste. Then, the paste is used to form a green sheet that becomes a magnetic body (soft magnetic metal sintered body) after firing. Next, silver (Ag) or the like that becomes a coil conductor is formed in a prescribed pattern on the formed green sheet. Next, after stacking a plurality of green sheets with coil conductor patterns, each coil conductor pattern is joined via a through hole, thereby obtaining a green laminated body in which the coil conductor is formed into a three-dimensional and spiral shape.

[0106] The obtained laminate is subjected to heat treatment (debinding process and sintering process) to remove the binder, thereby obtaining a sintered body (element) in which the soft magnetic metal particles contained in the soft magnetic metal powder are connected and fixed to each other (integrated). The holding temperature (debinding temperature) in the debinding process is not particularly limited as long as it is a temperature at which the binder can be decomposed and removed as a gas. For example, it can be above 300°C and below 450°C. In addition, the holding time (debinding time) in the debinding process is also not particularly limited. For example, it can be above 0.5 hours and below 2.0 hours.

[0107] The holding temperature (firing temperature) in the sintering process is not particularly limited as long as it is a temperature at which the soft magnetic metal particles constituting the soft magnetic metal powder are connected to each other. It can be 550°C or more and 850°C or less. In addition, the holding time (firing time) in the sintering process is also not particularly limited. It can be 0.5 hours or more and 3.0 hours or less.

[0108] In addition, the amount of phosphorus (P) contained in the soft magnetic metal particles after the heat treatment is consistent with the amount of phosphorus (P) contained in the soft magnetic metal particles before the heat treatment.

[0109] In addition, in the present embodiment, it is preferable to adjust the atmosphere during the binder removal and firing.

[0110] Annealing (heat treatment) may be performed after sintering. The conditions for annealing are not particularly limited. For example, the annealing may be performed at 500 to 800° C. for 0.5 to 2.0 hours. In addition, the atmosphere after annealing is not particularly limited.

[0111] It should be noted that the composition of the soft magnetic metal particles after the heat treatment is substantially the same as the composition of the soft magnetic metal powder before the heat treatment.

[0112] Next, terminal electrodes are formed on the element. The method for forming the terminal electrodes is not particularly limited, but they are usually prepared by slurrying a metal (Ag, etc.) to be the terminal electrodes together with an additive such as a solvent or a binder.

[0113] Next, when the magnetic body contains a resin, the resin is impregnated into the element to fill the gap space with the resin. The method of impregnating the resin is not particularly limited. For example, a method using vacuum impregnation can be used.

[0114] Vacuum impregnation is performed by immersing the above-mentioned laminated coil element in resin and controlling the air pressure. The resin penetrates into the magnetic body contained in the element by reducing the air pressure. In addition, since there is a gap space from the surface to the inside of the magnetic body, the resin penetrates into the inside of the magnetic body through the gap space by the principle of capillary phenomenon, especially the interlayer part where the resin is most difficult to penetrate, thereby filling the gap space with resin. Then, the resin is cured by heating. The heating conditions vary depending on the type of resin.

[0115] There is no particular restriction on the type of resin. It is preferred that the resin is eventually filled in the gap space. For example, especially when using phenolic resin or epoxy resin, the resin fully penetrates into the gap space inside the magnetic body (especially the interlayer part), and is easy to fully fill the gap space after curing. Furthermore, it will not decompose easily even if heated, so the heat resistance is also high. In contrast, when using silicone resin, the resin is particularly in a film-like state on the surface of the soft magnetic metal particles in the surface part, and it is difficult for the resin to fully penetrate into the gap space inside the magnetic body (especially the interlayer part). Furthermore, if heated above 300°C, the resin will decompose, so the heat resistance is also low.

[0116] The resin content in the magnetic body of the finally obtained laminated coil type electronic component is preferably 0.5 wt% to 3.0 wt%. The resin content can be controlled by, for example, changing the concentration of the resin solution during impregnation, the impregnation time, the number of impregnations, etc.

[0117] In this embodiment, the terminal electrodes can be electroplated after the resin is filled. Since the resin is filled in the gap space, even if the magnetic body is put into the plating solution, the plating solution is difficult to penetrate into the magnetic body. Therefore, even after plating, a short circuit will not occur inside the stacked coil type electronic component, and the inductance L is kept high.

[0118] (Second Embodiment)

[0119] Hereinafter, the second embodiment will be described, but points not particularly described are the same as those of the first embodiment.

[0120] The soft magnetic metal powder involved in the second embodiment is an aggregate of multiple soft magnetic metal particles. The soft magnetic metal particles are composed of Fe-Ni alloy. The Fe-Ni alloy further contains Cr. Moreover, the Fe-Ni alloy further contains Si and / or M. In the case of containing M, M is preferably Co. Moreover, in the present embodiment, in the Fe-Ni alloy, the total content of Fe, Ni, Si, M and Cr is set to 100% by mass, and the content of Cr is less than 2.0% by mass. The content of Cr can be 0.1% by mass or more and 1.8% by mass or less, or 0.5% by mass or more and 1.5% by mass or less.

[0121] In particular, when the Cr content is within the above-mentioned range, the magnetic permeability μ and the resistivity ρ become high.

[0122] The soft magnetic metal powder according to the second embodiment may further contain P. With the total content of Fe, Ni, Si, M, and Cr being 100 mass %, P may be contained in an amount of 100 ppm to 5000 ppm, or in an amount of 200 ppm to 2000 ppm.

[0123] Moreover, the content of Ni may be 15.0% by mass or more and 80.0% by mass or less, or 15.0% by mass or more and 55.0% by mass or less. In the case of containing Si, the content of Si may be 1.0% by mass or more and 6.0% by mass or less, or 2.0% by mass or more and 4.0% by mass or less. In the case of containing M, the content of M may be 1.0% by mass or more and 50.0% by mass or less, or 2.0% by mass or more and 40.0% by mass or less.

[0124] Furthermore, the content of Ni may be 22.0 mass % or more and 42.0 mass % or less. The content of Si may be 2.5 mass % or more and 5.5 mass % or less, or 2.5 mass % or more and 4.0 mass % or less. The content of M may be 5.0 mass % or more and 32.0 mass % or less. The content of P may be 300 ppm or more and 2000 ppm or less.

[0125] (Third Embodiment)

[0126] Hereinafter, a third embodiment will be described, but points not particularly described are the same as those of the first and second embodiments.

[0127] In the third embodiment, there is no particular limitation on the composition of the soft magnetic metal particles except that the Cr content is less than 2.0 mass % (excluding 0 mass %). The soft magnetic metal particles of the second embodiment may be used.

[0128] The coil-type electronic component involved in the third embodiment is a coil-type electronic component made using soft magnetic metal powder containing the soft magnetic metal particles. The coil-type electronic component is a coil-type electronic component having a magnetic body and a coil conductor built into the magnetic body. The magnetic body contains soft magnetic metal particles, and the soft magnetic metal particles are coated with a coating film. The coating film is composed of a first layer in contact with the above-mentioned soft magnetic metal particles and a second layer connected to the first layer. The first layer contains Si or an oxide containing Si, and the second layer contains Cr.

[0129] The coating film (oxide coating 11b) coated with the soft magnetic metal particles is composed of a first layer and a second layer, each of which has the above-mentioned composition, thereby improving the magnetic permeability μ and resistivity ρ of the soft magnetic metal sintered body composed of the soft magnetic metal particles. In addition, the Q value and inductance L of the coil-type electronic component having a magnetic body containing soft magnetic metal particles are improved.

[0130] However, when the Cr content in the soft magnetic metal particles is 2.0 mass % or more, the magnetic permeability μ is greatly reduced, and the Q value and inductance L of the coil-type electronic component are also reduced.

[0131] Compared with the soft magnetic metal particles, the first layer may contain more Si and less Fe. Compared with the soft magnetic metal particles, the second layer may contain more Si, Cr, and Ni and less Fe.

[0132] The average thickness of the first layer is set to D1, and the average thickness of the second layer is set to D2, so that 0.5≤D2 / D1≤1.5 can be satisfied. When D2 / D1 is within the above range, it is easy to form an oxide film of appropriate thickness, and the magnetic permeability μ and resistivity ρ of the soft magnetic metal sintered body are easy to become good.

[0133] D2 can be 2.5 nm or more and 30 nm or less, or 5 nm or more and 20 nm or less. When D2 is 30 nm or less, the magnetic permeability μ of the soft magnetic metal particles is easily increased, and the Q value and inductance L of the coil type electronic component are also easily increased. In addition, when D2 is 2.5 nm or more, the resistivity ρ of the soft magnetic metal particles is easily increased, and the plating elongation of the coil type electronic component is also easily suppressed.

[0134] There is no particular limitation on the method of coating the soft magnetic metal particles contained in the magnetic body with the above-mentioned coating film. For example, in addition to the method of forming the first layer and the second layer at the stage of the soft magnetic metal powder, a method of forming the first layer and the second layer on the surface of the soft magnetic metal particles by sintering can also be cited. By sintering the soft magnetic metal particles containing Si and Cr in a reducing atmosphere, the first layer and the second layer can be formed on the surface of the soft magnetic metal particles. It should be noted that if the sintering temperature is the same, the longer the sintering time and the lower the hydrogen concentration in the sintering atmosphere, the thicker the first layer and the second layer. If the sintering time is the same, the higher the sintering temperature and the lower the hydrogen concentration in the sintering atmosphere, the thicker the second layer. Furthermore, the more Cr is contained in the soft magnetic metal particles, the thicker the second layer.

[0135] The soft magnetic metal particles included in the coil-type electronic component of the second embodiment may be covered with a coating film similar to the soft magnetic metal particles included in the coil-type electronic component of the third embodiment.

[0136] As mentioned above, although embodiment of this invention was described, this invention is not limited to the said embodiment, It can change in various aspects within the scope of this invention.

[0137] As coil-type electronic components, transformers, choke coils, coils, etc. are known. The coil-type electronic component according to the present embodiment can be suitably used in power supply circuits of various electronic devices such as portable devices as inductors and resistors.

[0138] Example

[0139] Hereinafter, the present invention will be described in more detail using examples, but the present invention is not limited to these examples.

[0140] (Experimental Example 1)

[0141] First, Fe-Ni alloy, Fe element, Ni element, Si element, and M element were prepared as raw materials. Each alloy and / or element was in the form of an ingot, a thick block, or a shot. Then, these raw materials were mixed in a manner to form the composition shown in Tables 1 to 3, and stored in a crucible disposed in a water atomization device. In addition, Examples 2b to 2p in Table 3 are examples implemented under the same conditions except that the type of M in Example 2 was changed.

[0142] Next, the crucible is heated to 1600°C or higher by high-frequency induction using a working coil disposed outside the crucible under an inert atmosphere, and the ingot, slab or shot in the crucible is melted and mixed to obtain a molten metal. It should be noted that the phosphorus content is adjusted by adjusting the amount of phosphorus contained in the raw material of the Fe element when the raw material of the soft magnetic metal powder is melted and mixed.

[0143] Next, a high-pressure (50 MPa) water flow was made to collide with the molten metal supplied from a nozzle provided in the crucible in a linear continuous flow, and the molten metal was rapidly cooled while being dropletized, and then dehydrated, dried, and classified to produce a soft magnetic metal powder composed of Fe-Ni-Si-M alloy particles. The average particle size (D50) of the soft magnetic metal powder was the value described in Tables 1 to 3.

[0144] The obtained soft magnetic metal powder was analyzed by ICP analysis, and it was confirmed that the soft magnetic metal powder used in each example and comparative example had the composition described in Tables 1 to 3. Furthermore, it was confirmed that elements other than Fe, Ni, Si, M and P, such as Cr, were substantially not contained.

[0145] An acrylic resin as a binder was added to the obtained soft magnetic metal powder to prepare granulated powder. The granulated powder was used to form a ring shape with an outer diameter of 13 mm, an inner diameter of 6 mm, and a height of 2.7 to 3.3 mm, and a molding pressure of 6 ton / cm 2 Molding is performed. Next, the molded body is maintained at 400°C in an inert atmosphere to remove the binder, and then the molded body after the debinding is sintered at 750°C-1h in a reducing atmosphere (a mixed gas atmosphere of N2 gas and H2 gas with a hydrogen concentration of 1.0%) to obtain a sintered body. It should be noted that the above-mentioned inert atmosphere is an N2 gas atmosphere, and the above-mentioned reducing atmosphere is a mixed gas atmosphere of N2 gas and H2 gas. In addition, the hydrogen concentration in the above-mentioned mixed gas atmosphere is 1.0%. Furthermore, the obtained sintered body is heat treated at 700°C-1h in an atmosphere with an oxygen partial pressure of 1%, thereby obtaining a sintered body for evaluation.

[0146] The magnetic permeability (μ) and the resistivity (ρ) of the obtained sintered body for evaluation were measured by the following methods.

[0147] The magnetic permeability was measured by a coaxial method at f=2 MHz using a radio frequency (RF) impedance / material analyzer (manufactured by Agilent Technologies: 4991A).

[0148] For μ of each comparative example (Comparative Example 8, Comparative Example 1, Comparative Example 10, Comparative Example 12) with a P content of 50 ppm in Table 1, the increase ratio (Δμ / μ) of μ in samples with the same conditions except for the P content was calculated. Samples with Δμ / μ of 20.0% or more were considered good.

[0149] In Comparative Examples 3 and 4, Examples 2, 5 to 6, 5a, and 6a in Table 2, Δμ / μ in samples with different Si contents, etc., was calculated for μ in Comparative Example 3 having a Si content of 1.5 mass %. Samples with Δμ / μ of 20.0% or more were rated as good.

[0150] In Comparative Examples 5, 6a, 6, Examples 7 to 10, 7a, and 9a in Table 2, Δμ / μ in samples with different Co contents was calculated relative to μ in Comparative Example 5 having a Co content of 1.0 mass %. Samples with Δμ / μ of 20.0% or more were considered good.

[0151] In Comparative Examples 7 and 7a and Examples 11 and 12 in Table 2, Δμ / μ in samples with different Ni contents was calculated relative to μ in Comparative Example 7 having a Ni content of 56.0 mass %. Samples with Δμ / μ of 20.0% or more were rated as good.

[0152] In Table 3, the increase ratio (Δμ / μ) of μ in samples having the same conditions except for the P content and the type of M was calculated relative to μ in Comparative Example 1 having a P content of 50 ppm. Samples having a Δμ / μ of 20.0% or more were rated as good.

[0153] ρ was calculated from the volume and DC resistance of the sintered body by coating In-Ga electrodes on both sides of the obtained sintered body and measuring the DC resistance with an ultra-high resistance meter (R8340 manufactured by ADVANTEST). A value of ρ of 1.0E06 Ω·m or more was considered good.

[0154] Table 1

[0155]

[0156] Table 2

[0157]

[0158] Table 3

[0159]

[0160] According to Table 1 and Table 3, each embodiment in which the P content is 100 ppm or more and 5000 ppm or less has good μ and ρ compared with the comparative example in which the P content is 50 ppm. In contrast, the ρ of the comparative example in which the P content is 50 ppm becomes low. In addition, the comparative example in which the P content is 6000 ppm has a tendency to have lower μ and lower ρ compared with the embodiments in which the P content is 100 to 5000 ppm and the other conditions are the same.

[0161] According to Table 2, each Example in which the content of each component is within the prescribed range tends to have better μ and ρ than each Comparative Example in which the content of Ni, Si and / or Co is outside the prescribed range.

[0162] (Experimental Example 2)

[0163] Experimental Example 2 was carried out in the same manner as Experimental Example 1, except that a single substance of Cr was further prepared as a raw material and it was confirmed that the soft magnetic metal powder did not substantially contain elements other than Fe, Ni, Si, M, Cr, and P.

[0164] In Tables 4 to 6, the increase ratio (Δμ / μ) of μ in the samples having a Cr content of less than 2.0 mass% was calculated relative to μ in Comparative Example 537 having a Cr content of 2.0 mass%. Samples having a Δμ / μ of 20.0% or more were rated as good.

[0165] Examples 538 to 542 in Table 4 are examples obtained by mainly changing the content of Cr from Comparative Example 537. Examples 543 to 546 and 544a in Table 4 are examples obtained by mainly changing the content of Si from Example 540. Examples 547 to 550 in Table 5 are examples obtained by changing the content of P from Example 540. Examples 540b to 540p in Table 6 are examples obtained under the same conditions as Example 540 except that the type of M was changed.

[0166] [Table 4]

[0167] Table 4

[0168]

[0169] [Table 5]

[0170]

[0171] [Table 6]

[0172]

[0173] According to Tables 4 to 6, each of the Examples having a Cr content of less than 2.0 mass % has better μ and ρ than Comparative Example 537 having a Cr content of 2.0 mass %.

[0174] (Experimental Example 3)

[0175] The soft magnetic metal powder prepared in Experimental Example 1 was slurried with additives such as a solvent and a binder to prepare a paste. The types of soft magnetic metal powders are shown in Tables 7 to 10. Then, the paste was used to form a green sheet that became a magnetic body after firing. A predetermined pattern of Ag conductors (coil conductors) was formed on the green sheet, and a green laminate with a thickness of 0.8 mm was prepared by stacking.

[0176] Next, the obtained green laminated body is cut into a shape of 2.0 mm × 1.2 mm to obtain a green laminated coil. The obtained green laminated coil is subjected to a debinding treatment at 400°C under an inert atmosphere (N2 gas atmosphere). Then, the samples described in Tables 7 to 9 are sintered at 750°C-1h under a reducing atmosphere (a mixed gas atmosphere of N2 gas and H2 gas (hydrogen concentration 1.0%)) to obtain a sintered body. The samples described in Table 10 are sintered at the sintering temperature, sintering time and sintering atmosphere described in Table 10 to obtain a sintered body. The terminal electrode paste is applied to both end surfaces of the obtained sintered body and dried, and sintered at 700°C for 1 hour in an atmosphere with an oxygen partial pressure of 1% to form terminal electrodes, thereby obtaining a laminated coil (sintered product).

[0177] Next, in the examples and comparative examples described in Tables 7 to 10 below, each of the obtained sintered products was impregnated with resin. Specifically, a raw material mixture of phenolic resin or epoxy resin was vacuum impregnated, and then heated to cure the resin at 150°C-2h, thereby filling the resin. In addition, when the resin is cured, the solvent contained in the raw material mixture evaporates. Thereafter, electrolytic plating was performed to form a Ni plating layer and a Sn plating layer on the terminal electrode.

[0178] In addition, the raw material mixture of the phenolic resin is about 50% by weight of phenols (C7H8O.CH2O.C4H 10 O) x , about 38% by weight of ethylene glycol monobutyl ether, about 11% by weight of 1-butanol, about 0.20% by weight of formaldehyde, and about 0.1% of m-cresol. The raw material mixture of the epoxy resin is a mixture of a naphthalene-type epoxy resin, a curing agent, a solvent (toluene), etc.

[0179] Then, the inductance L and Q value of the laminated coils of each example and comparative example were measured using an LCR meter (manufactured by HEWLETT PACKARD: 4285A) at f = 2 MHz and I = 0.1 A. The L and Q values ​​listed in Tables 7 to 10 are the average values ​​of the L and Q values ​​of 30 laminated coils.

[0180] Table 7 shows the increase ratio (ΔL / L) of L in the laminated coil with the same conditions except for the content of P relative to L in the comparative examples (Comparative Examples 102 and 103) with a P content of 50 ppm. A value of ΔL / L of 20.0% or more was considered good.

[0181] In Table 8, ΔL / L in samples with different Si contents was calculated relative to L in Comparative Example 111 having a Si content of 1.5 mass % in Comparative Examples 111, 112, Examples 111 to 113, 111a, and 112a. Samples with ΔL / L of 20.0% or more were rated as good.

[0182] In Comparative Examples 113 to 115, Examples 114 to 117, 114a, and 116a, ΔL / L in samples with different Co contents was calculated relative to L in Comparative Example 113 having a Co content of 1.0 mass %. Samples with ΔL / L of 20.0% or more were considered good.

[0183] In Comparative Examples 116 and 117 and Examples 118 and 119, ΔL / L in samples with different Ni contents was calculated relative to L in Comparative Example 116 having a Ni content of 56.0 mass %. Samples with ΔL / L of 20.0% or more were rated as good.

[0184] In Table 9, ΔL / L in samples having the same conditions except for the P content and the type of M was calculated relative to L in Comparative Example 102 having a P content of 50 ppm. Samples having a ΔL / L of 20.0% or more were rated as good.

[0185] Regarding Table 10, ΔL / L was calculated for Examples 121 to 126 in which the firing conditions of Example 116 were changed as also described in Table 8, relative to Comparative Example 113 as also described in Table 8. Samples with ΔL / L of 20.0% or more were rated as good.

[0186] A Q value of the laminated coil of 40.0 or more was considered good.

[0187] For the laminated coils of each embodiment and comparative example, the plating elongation was evaluated. The evaluation of the plating elongation was performed by observing the appearance of the laminated coil. The case where no plating elongation was observed was recorded as A, the case where the plating elongation was observed to be 50 μm or less was recorded as B, the case where the plating elongation exceeded 50 μm and was less than 400 μm was recorded as C, and the case where the plating elongation was 400 μm or more was recorded as D, and recorded in Tables 7 to 10. In Experimental Example 3 and Experimental Example 4 described later, the case where the plating elongation was evaluated as A or B was set as good, and the case where it was A was set as particularly good.

[0188] The short circuit rate of the laminated coils of each embodiment and comparative example was measured. 30 laminated coils were prepared for each sample, and the number of laminated coils that were short-circuited was measured using an LCR meter to calculate the short circuit rate. When the short circuit rate was 3% or less, that is, 0 / 30, it was considered good.

[0189] The average thickness of the coating film was measured for the laminated coils listed in Table 10. The average thickness of the coating film was measured by appropriately combining observation of the cross section of the interlayer portion at a size of 7 μm × 7 μm at a magnification of 20,000 times using STEM-EDS and observation at a size of 0.3 μm × 0.3 μm at a magnification of 500,000 times. Specifically, the thickness of the coating film of at least 50 soft magnetic metal particles 11 was measured using STEM-EDS in the cross section of the interlayer portion and averaged.

[0190]

[0191]

[0192]

[0193]

[0194] According to Tables 7 and 9, the L and Q values ​​of the laminated coils made from the soft magnetic metal powders of Comparative Examples 1 and 2 were not appropriate. Furthermore, the plating elongation was also inferior to that of the Examples in Tables 7 and 9.

[0195] According to Table 8, Examples 111 to 119, Examples 111a, 112a, 114a, 116a, and Comparative Examples 111 to 117, when the laminated coils were made using the soft magnetic metal powders of Comparative Examples 3 to 7, 6a, and 7a, the L and / or Q values ​​were lower than when the laminated coils were made using the soft magnetic metal powders of Examples 2 to 12, 5a, 6a, 7a, and 9a. Furthermore, when the soft magnetic metal powder of Comparative Example 3 having an excessively low Si content was used, the plating elongation and short circuit rate were also poor.

[0196] According to Table 10, Examples 116, and 121 to 126, the shorter the firing time and the higher the hydrogen concentration of the firing atmosphere, the higher μ and lower ρ of the fired body tend to be. Furthermore, the L of the laminated coil tends to be higher and the coating thinner.

[0197] It is to be noted that the average thickness of the coating films in the Examples described in Tables 7 to 9 was confirmed to be approximately 40 nm.

[0198] (Experimental Example 4)

[0199] The presence or absence of resin filling in the interlayer gap space was confirmed for the laminated coils of Examples 103 and 104. Specifically, a cross-sectional photograph of the interlayer portion was taken at a magnification of 10,000 times and a size of 13 μm×10 μm using an SEM and observed. Figure 3 is a SEM image of the interlayer portion in the laminated coil of Example 103. Figure 4 This is a SEM image of the interlayer portion in the laminated coil of Example 104. It can be seen that the gap space in the interlayer portion is filled with resin in both Examples 103 and 104.

[0200] Furthermore, the laminated coil of Example 103 was observed using STEM-EDS at a magnification of 20,000 times, which is higher than the above measurement, and at a size of 7 μm × 7 μm. Furthermore, the observation was performed at a magnification of 500,000 times and at a size of 0.3 μm × 0.3 μm. The results are shown in Figure 5 to Figure 12 . Figure 5 This is the BF image at a magnification of 20,000 times; Figure 6 This is the BF image at a magnification of 500,000 times; Figure 7 This is a C mapping image at a magnification of 20,000 times; Figure 8 This is a C mapping image at a magnification of 500,000 times; Fig. 9 This is the Si mapping image at a magnification of 20,000 times; Fig.10 This is the Si mapping image at a magnification of 500,000 times; Fig.11 This is the O mapping image at a magnification of 20,000 times; Fig.12 This is an O mapping image at a magnification of 500,000 times.

[0201] From these images, it can be seen that the main body of the soft magnetic metal particles is coated with an oxide film as a type of coating film, and the layer in the oxide film that contacts the main body of the soft magnetic metal particles is composed of Si or an oxide containing Si. Furthermore, it can be seen that Si is substantially contained only in the main body of the soft magnetic metal particles and the coating film, and C is substantially contained only in the resin filled in the gap space. In addition, in all the examples described in Tables 7 to 9, it was confirmed that the average thickness of the coating film was 5 nm or more and 60 nm or less.

[0202] (Experimental Example 5)

[0203] The soft magnetic metal powder prepared in Experimental Example 2 was slurried together with additives such as solvents and adhesives to prepare a paste. A stacked coil was prepared in the same manner as in Experimental Example 3. Regarding the firing conditions, the samples described in Tables 11 to 13 were fired at 750°C-1h in a reducing atmosphere (a mixed gas atmosphere of N2 gas and H2 gas (hydrogen concentration 1.0%)) to obtain a fired body. The samples described in Table 14 were fired at the firing temperature, firing time, and firing atmosphere described in Table 14 to obtain a fired body. The Q value of the stacked coil is considered to be 40.0 or above and is considered to be good.

[0204] In addition, in the laminated coils described in Tables 11 to 14, the coating film was observed in the same manner as in the laminated coil described in Table 10. Then, D1 and D2 were measured, and D2 / D1 was calculated. It should be noted that in all the examples described in Tables 11 to 14 (except for Examples 116 and 116c), it was confirmed that the content of Si in the first layer was higher than that of the soft magnetic metal particles, and the content of Fe was lower, and the content of Si, Cr, and Ni in the second layer was higher than that of the soft magnetic metal particles, and the content of Fe was lower.

[0205] In Experimental Example 5, the increase ratio (ΔL / L) of L in a laminated coil having a Cr content of less than 2.0 mass% and the same resin type as the comparative example was calculated relative to L in the comparative example (Comparative Examples 601 and 602) having a Cr content of 2.0 mass%. The case where ΔL / L is 20.0% or more is considered good.

[0206]

[0207]

[0208]

[0209]

[0210] According to Tables 11 to 13, the L and Q values ​​of the laminated coil made from the soft magnetic metal powder of Comparative Example 537 did not reach appropriate values. In addition, the laminated coils of Examples 116 and 116c made from the soft magnetic metal powder of Example 9 that does not contain Cr have a structure in which the coating film consists of only the first layer. In addition, compared with other Examples that have the same conditions except for the Fe content and the Cr content, the Q value is low.

[0211] As can be seen from Table 12, if the Cr content is the same, there is a tendency that as the Si content increases, D1 becomes larger and D2 becomes smaller.

[0212] According to Table 14, Examples 608, and 631 to 636, it can be seen that the shorter the firing time and the higher the hydrogen concentration of the firing atmosphere, the higher the μ of the fired body and the lower the ρ. Furthermore, there is a tendency that the L of the stacked coil becomes higher and the coating becomes thinner. In addition, according to Examples 608, 637 to 640, it can be seen that the higher the firing temperature and the lower the hydrogen concentration of the firing atmosphere, the lower the μ of the fired body and the higher the ρ. Furthermore, there is a tendency that the L of the stacked coil becomes lower, the coating becomes thicker, and D2 / D1 becomes higher.

Claims

1. A soft magnetic metal powder, characterized in that: The soft magnetic metal powder comprises soft magnetic metal particles composed of Fe-Ni alloy. The Fe-Ni alloy further comprises Cr and M, M is Co, The Fe-Ni alloy contains 15.0 mass % to 80.0 mass % Ni, less than 2.0 mass % Cr, and 1.0 mass % to 50.0 mass % M, based on the total content of Fe, Ni, Si, M and Cr being 100 mass %.

2. The soft magnetic metal powder according to claim 1, characterized in that The Fe—Ni alloy further contains Si, and the content of Si is 1.0 mass % or more and 6.0 mass % or less.

3. The soft magnetic metal powder according to claim 1 or 2, characterized in that: The Fe-Ni alloy further comprises P, The Fe-Ni alloy contains P in an amount of 100 ppm to 5000 ppm inclusive, based on a total content of Fe, Ni, Si, M, and Cr being 100 mass %.

4. The soft magnetic metal powder according to claim 1 or 2, characterized in that: The soft magnetic metal powder has an average particle size D50 of 1.5 μm or more and 15.0 μm or less.

5. A soft magnetic metal sintered body, characterized in that: The invention comprises the soft magnetic metal powder according to any one of claims 1 to 4.

6. A coil type electronic component, characterized in that: The coil-type electronic component includes a magnetic body and a coil conductor built into the magnetic body. The magnetic body is composed of the soft magnetic metal sintered body according to claim 5.

7. The coil type electronic component according to claim 6, characterized in that: The soft magnetic metal particles are coated with a coating film, The layer in the coating film that is in contact with the soft magnetic metal particles contains Si or an oxide containing Si.

8. The coil type electronic component according to claim 7, characterized in that: The layer in the coating film that is in contact with the soft magnetic metal particles further contains P.

9. The coil type electronic component according to claim 7 or 8, characterized in that: The average thickness of the coating film is 5 nm or more and 60 nm or less.

10. The coil type electronic component according to claim 7 or 8, characterized in that: The magnetic body comprises soft magnetic metal particles and resin. The resin fills the interstitial spaces between the soft magnetic metal particles.

11. The coil type electronic component according to claim 10, characterized in that: The resin is phenolic resin or epoxy resin.

12. A coil type electronic component, characterized in that: The coil-type electronic component includes a magnetic body and a coil conductor built into the magnetic body. The magnetic body comprises soft magnetic metal particles. The soft magnetic metal particles contain Ni in an amount of 15.0 mass % or more and 80.0 mass % or less, and contain Cr in an amount of less than 2.0 mass % but excluding 0 mass %. The soft magnetic metal particles are coated with a coating film, The coating film is composed of a first layer in contact with the soft magnetic metal particles and a second layer in contact with the first layer. The first layer comprises Si or an oxide containing Si, The second layer comprises Cr, When the average thickness of the first layer is recorded as D1 and the average thickness of the second layer is recorded as D2, 0.8≤D2 / D1≤1.

5.

13. The coil type electronic component according to claim 12, characterized in that: D2 is greater than or equal to 2.5 nm and less than or equal to 30 nm.

14. The coil type electronic component according to claim 12, characterized in that: The magnetic body comprises soft magnetic metal particles and resin. The resin fills the interstitial spaces between the soft magnetic metal particles.

15. The coil type electronic component according to claim 14, characterized in that: The resin is phenolic resin or epoxy resin.